2012
DOI: 10.17221/5566-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between longevity and conformation traits in the Czech Holstein population

Abstract: Genetic correlations between longevity and conformation traits were estimated using data on Czech Holstein cows first calved in the years 1993–2008. Longevity traits considered were length of productive life and number of lactations initiated and their functional equivalents (i.e. the longevity traits corrected for milk production). Conformation traits were twenty one linear descriptive type traits, six composite traits and height at sacrum measured in cm. A possible nonlinear relationship between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
47
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 26 publications
12
47
1
5
Order By: Relevance
“…The means of composite traits ranged from 78.10 (SD = 4.52) for overall udder score to 81.95 (SD = 4.16) for size, and showed that the conformation of Polish cows corresponded well with the conformation standard. The means of most composite traits in our study were similar to those obtained by Ptak et al (2011) for the Polish population and Zavadilova and Stipkova (2012) for Czech Holstein cows. The average for stature of Polish HF cows was 143 cm (Table 1), slightly less than the mean obtained by Lassen and Mark (2008) for Danish Holstein cows (144.3 cm).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The means of composite traits ranged from 78.10 (SD = 4.52) for overall udder score to 81.95 (SD = 4.16) for size, and showed that the conformation of Polish cows corresponded well with the conformation standard. The means of most composite traits in our study were similar to those obtained by Ptak et al (2011) for the Polish population and Zavadilova and Stipkova (2012) for Czech Holstein cows. The average for stature of Polish HF cows was 143 cm (Table 1), slightly less than the mean obtained by Lassen and Mark (2008) for Danish Holstein cows (144.3 cm).…”
Section: Resultssupporting
confidence: 86%
“…The range of heritabilities for composite traits was similar to the results of the previous study in Polish Holsteins: from 0.11 for overall feet and leg score to 0.39 for size (Ptak et al 2011). Zavadilova and Stipkova (2012) also reported the lowest heritability for feet and legs (0.12), but they estimated the highest heritability not for size as in this paper but for dairy form (0.28).…”
Section: Resultsmentioning
confidence: 42%
“…Estimated heritability for LPL within herds was small (0.09) but higher than the value of 0.03 reported by Zavadilová and Štípková (2012) for Czech Holsteins or 0.04 by Páchová et al (2005). The within-herd heritability reported in our study was similar to results of Vollema and Groen (1998), who reported an estimate of 0.07 in Danish Holsteins using linear model analysis of functional longevity.…”
Section: Heritabilitysupporting
confidence: 53%
“…In their study du Toit et al (2012) reported a similar value of -0.19 for genetic correlations between body depth and number of lactations in Jerseys. Higher genetic correlations between longevity and body depth than in the present study were -0.23 for Czech Holstein by Zavadilova and Stipkova (2012), -0.26 for Holstein by Kern et al (2015), and 0.28 for Austrian Fleckvieh (Fuerst et al 2013). For Aosta Red Pied, Mazza et al (2016) found medium negative genetic correlations between test-day milk, fat and protein yield, and muscularity conformation score in dual-purpose cattle, values of -0.42, -0.37, -0.34, respectively.…”
Section: Resultscontrasting
confidence: 46%